PENYUSUNAN LAPORAN KEUANGAN SESUAI STANDAR SAK EMKM PADA UMKM â€œNIKY COKLATâ€ KEDIRI (Fakultas Ekonomi Universitas Islam Kadiri (UNISKA) Kediri, 2024)
Abstract This research focuses on the application of Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) to the